Analysis of miRNA and mRNA reveals core interaction networks and pathways of dexamethasone-induced immunosuppression in chicken bursa of Fabricius. (June 2021) - Su, Aru; Guo, Yujie; Tian, Huihui; Zhou, Yanting; Li, Wenting; Tian, Yadong; Li, Kui; Sun, Guirong; Jiang, Ruirui; Yan, Fengbin; Kang, Xiangtao
Highlights: Dexamethasone-Induced immunosuppression models were constructed in Gushi cocks. MiR-103-3p, miR-456-3p and miR-15/17 family were essential miRNAs. Some DEGs, such as SIKE1, HMGA2, IL6, SOCS3, ITGB5 were crucial mRNAs. Gga-miR-20b-5p negatively regulated SIKE1 may play a role in immunosuppression. Abstract: Stress-induced immunosuppression is a serious problem affecting the production value of poultry, but its specific molecular mechanism has not yet been elucidated. We selected 7-day-old Gushi cocks as test animals and successfully established a stress-induced immunosuppression model by injecting 2.0 mg/kg (body weight) dexamethasone (Dex). We then constructed six cDNA libraries and two small RNA libraries of Bursa of Fabricius from the control group and the Dex group. RNA-seq results revealed 21, 028 transcripts including 3920 novel transcripts; 500 miRNAs including 68 novel miRNAs were identified. Correlation analysis of miRNA, target genes and mRNA results indicated that the gga-miR-15 family, gga-miR-103-3p, gga-miR-456-3p, and gga-miR-27b-3p, as core differentially expressed miRNAs, may potentially regulate multiple genes which are involved in immune-related pathways; and that the core genes Suppressor of IKBKE 1 ( SIKE1 ) and high mobility group AT-hook 2 ( HMGA2 ) are associated with the miR-17 family (gga-miR-20a-5p, gga-miR-20b-5p, gga-miR-106-5p, and gga-miR-17-5p) and gga-let -7 family (gga-let-7b, gga-let-7i, gga-let-7c-5p, and gga-let-7f-5p). The interaction networks of mRNAs of significantly enrichment pathways and PPI (protein-protein interaction) networks showed that IL6, IL1B, IL8L1, CCL5, SOCS3, SOCS1, ITGB5, GSTA3, SQLE, FDFT1, FN1, IL18, IL10, MAPK11 and MAPK12 are network core nodes and that most of them are strongly associated with immune response. One of the candidate miRNAs, gga-miR-20b-5p, may play an important role in stress-induced immunosuppression. Luciferase assay and over-expression experiments suggested that gga-miR-20b-5p negatively regulated the expression of target gene SIKE1 . These results provide better understanding of the mechanism of stress-induced immunosuppression in Gushi chicken bursa, and provide novel targets for subsequent research to improve poultry anti-stress capability.